Structural Reforms in Latin America under Scrutiny - Eduardo Lora; Ugo Panizza (Inter-American Development Bank, Research Department, 2002)
The future of structural reforms in Latin America is under discussion. The purpose of this document is to synthesize the facts and opinions that underlie this debate. The first section shows that although the reform process has not ground to a halt, it has been incomplete and uneven, both across countries and different areas of reform. The greatest progress has been made in reforming the trade and financial sectors. In terms of tax reform and privatization, the record has been mixed across countries. The most modest progress has been made in the area of labor code reform. The second section analyzes the status of public opinion of the reform process. Disillusionment with the reforms has been growing, particularly among the middle class. This disapproval, rather than reflecting concerns about the state of the economy or the degree of progress of the reforms, stems from the corruption that has tainted the privatization process in some countries. The third section reviews the effects of the reforms. Their impact on growth seems to have been positive, albeit temporary, but the effects on employment and income distribution have varied in different areas of reform and according to the particular context in each country. Specifically, the effectiveness of reforms has depended heavily on the quality of public institutions. The fourth section summarizes the main proposals to expand or reorient the reform agenda in the region. One set of proposals suggests broadening the Washington Consensus with more active policies aimed at addressing the need for greater economic stability, social integration and equitable income distribution. Another set of proposals, guided by a more encompassing view of the goals of development, emphasizes the interaction among civil society, the private sector, and the government. Finally, a more radical vision proposes a new national and international institutional architecture that would limit the role of markets and mitigate the effects of globalization. – – El futuro de las reformas estructurales en América Latina está en discusión. El objeto de este documento es resumir los hechos y las opiniones subyacentes de este debate. La primera parte muestra que si bien el proceso de reforma no se ha detenido del todo, sí ha sido incompleto y desigual, tanto entre países como entre las diversas áreas de reforma. Los mayores avances se han registrado en la reforma de los sectores del comercio internacional y las finanzas. En términos de reforma tributaria y privatización, los resultados de un país a otro son encontrados. Los avances más peque\~nos se han registrado en el área de la reforma del código laboral. En la segunda parte se analiza la situación de la opinión pública sobre el proceso de reforma. La desilusión con las reformas ha venido en aumento, especialmente entre la clase media. Más que reflejar inquietudes sobre el estado de la economía o el grado de avance de las reformas, esta crítica tiene que ver con la corrupción que ha empa\~nado el proceso de privatización en algunos países. En la tercera sección se pasa revista a los efectos de las reformas. Sus repercusiones en el crecimiento parecen haber sido positivas, aunque pasajeras, pero sus efectos en el empleo y la distribución del ingreso han variado en diversas áreas de la reforma y según el contexto específico de cada país. En particular, la eficacia de las reformas ha dependido en gran medida de la calidad de las instituciones públicas. En la cuarta parte se presenta una síntesis de las principales propuestas para ampliar o reorientar el programa de reformas en la región. Un conjunto de propuestas sugiere ampliar el Consenso de Washington con políticas más activas, destinadas a acometer la necesidad de mayor estabilidad económica, integración social y una distribución equitativa del ingreso. Otro conjunto de propuestas, guiado por un punto de vista más amplio de los objetivos del desarrollo, hace hincapié en la interacción entre la sociedad civil, el sector privado y el gobierno. Por último, una visión más radical propone una nueva estructura nacional e internacional de las instituciones, a fin de limitar el papel de los mercados y atenuar los efectos de la globalización.
Keywords: 330; Wirtschaftsreform; Privatisierung; Wirkungsanalyse; Lateinamerika